Evaluation of oral health services and challenges faced by oral health practitioners working in Nyarugenge, Rwanda. - Emmanuel Nzabonimana; Yolanda Malele-Kolisa; Phumzile Hlongwa (PLoS ONE)
Objective Oral healthcare professionals encounter considerable challenges while providing services to curb the oral disease burden. The aim of this study was to explore the challenges faced by oral health practitioners providing oral health services in Nyarugenge, Rwanda and to appraise the availability and adequacy of oral hygiene equipment, instruments, and materials. Methods This was a cross-sectional concurrent mixed methods study. The quantitative and qualitative parts were independent during data collection and analyses and merged during the interpretation phase. All seven public health facilities and 14 dental professionals working in Nyarugenge were included in the study. Data were collected using an audit checklist and an in-depth interview guide. Descriptive statistics were used to analyze the quantitative data. The interviews were analyzed using thematic content analysis. Results Most of the dental health professionals were dental therapists (n = 11), women (n = 9), aged 31-40 years (n = 7), and with 11-20 years' experience as oral health practitioners (n = 6). There were five health centers and two hospitals that were audited for equipment, instruments, and materials. The audit of the facilities revealed that most facilities have dental equipment and instruments, but none have adequate preventive dental instruments and materials. Four broad themes emerged from the interviews with the oral health practitioners, namely human resources, supply chain management, patients' oral health awareness and service rendering, and strategic management and administration. The most significant challenges oral health practitioners faced included high dental practitioner/patient ratios, lack of adequate and appropriate equipment and materials, patients' lack of oral health awareness, and a lack of administrative support. Conclusions Well-established community preventive interventions, such as a mobile oral health App, could reduce the patient/provider ratio by increasing population awareness of oral health and encouraging healthy behaviours. The management of the health facilities should address the human resource challenges and equipment supply chain issues.